Does Comprehensive Geriatric Assessment (CGA) have a role in UK care homes? - Gordon, Adam L. (2012)
UK care home residents are frail, dependent and multimorbid. General practitioners (GPs) provide their healthcare but there is evidence that existing provision fails to meet their needs. Comprehensive Geriatric Assessment (CGA) comprises comprehensive multidisciplinary assessment, goal setting and frequent review. This thesis considers a possible role for CGA in UK care homes through three research projects.